Decision to adopt online collaborative learning tools in higher education: A case of top Malaysian universities - Yadegaridehkordi, Elaheh; Shuib, Liyana; Nilashi, Mehrbakhsh; Asadi, Shahla (Springer, 2019)
Recently cloud computing has received significant attention, but its adoption is still far from reaching its full potential, especially in educational contexts. Only a few studies have considered the students’ behavior toward adoption of cloud technology in particular for online collaborative learning purposes. Therefore, this research seeks to develop an adoption model for online collaborative learning tools in cloud environment. To this end, Technology Acceptance Model (TAM) is extended by adding mobility, collaboration, and personalization as external variables. A sample of 209 respondents is collected from four top Malaysian universities and Structural Equation Modelling (SEM) is utilized to assess the research model. The findings show that intention to adopt is significantly affected by perceived usefulness. Although, perceived ease of use does not perform a direct impact on intention to adopt, its indirect influence through perceived usefulness is supported. Mobility and personalization significantly influence perceived ease of use, but they have insignificant impacts on perceived usefulness. Furthermore, perceived usefulness and perceived ease of use are significantly influenced by collaboration. This study rounds off with discussion and conclusions, highlighting implications. The findings provide a baseline for cloud service providers and education institutions in providing effective online collaborative learning tools. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.